2015
DOI: 10.5505/tjb.2015.44227
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of a new thermostable lipase from Bacillus pumilus strain

Abstract: Objective: Research and characterization of new thermostable lipases from bacterial strains isolated from tannery waters in the old medina of Fez. Methods: Gene which encodes the 16S ribosomal RNA for a bacterial species was amplified via PCR and sequenced (Bacillus pumilus HF544325). The extracellular lipase from B. pumilus is purified by gel filtration (Sephacryl S-200) and cation exchange chromatography (Mono S sepharose cation exchanger). The N-terminal sequences of purified Bacillus pumilus lipase were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
3
2
0
Order By: Relevance
“…The Sephacryl S‐200 column chromatography was very effective for lipase purification due to the increase of the fold purification to 97.43. In accordance with our results, lipase from B. pumilus purified by four purification steps (ammonium sulfate precipitation, heat treatment, Sephacryl S‐200, and Mono‐S chromatography) reached 210‐fold with enzyme yield of 36% (Faouzi et al, 2015). Our results proved that the overall yield of 22.07% was higher than lipases extracted from different Bacillus strains, such as B. licheniformis SCD11501 (8.4%) (Sharma and Kanwar, 2017) and B. subtilis NS 8 (16%) (Olusesan et al, 2011), but approximately similar to B. licheniformis MTCC‐10498 (24%) (Sharma and Kanwar, 2012).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The Sephacryl S‐200 column chromatography was very effective for lipase purification due to the increase of the fold purification to 97.43. In accordance with our results, lipase from B. pumilus purified by four purification steps (ammonium sulfate precipitation, heat treatment, Sephacryl S‐200, and Mono‐S chromatography) reached 210‐fold with enzyme yield of 36% (Faouzi et al, 2015). Our results proved that the overall yield of 22.07% was higher than lipases extracted from different Bacillus strains, such as B. licheniformis SCD11501 (8.4%) (Sharma and Kanwar, 2017) and B. subtilis NS 8 (16%) (Olusesan et al, 2011), but approximately similar to B. licheniformis MTCC‐10498 (24%) (Sharma and Kanwar, 2012).…”
Section: Resultssupporting
confidence: 91%
“…Generally, bacterial lipases require an alkaline or neutral pH for their metabolic processes (Bharathi and Rajalakshmi, 2019). Similar results have been reported where Bacillus subtili s (Saraswat et al, 2017) and B. pumilus HF544325 (Faouzi et al, 2015) showed maximum production of lipase at pH 8.0. However, a high lipase productivity has been yielded by culture media with at pH 10.0 and 11.0 for B. subtilis 168 (Lesuisse and Schanck, 1993) and Bacillus flexus XJU‐1 (Niyonzima and More, 2015), respectively.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…S1E29, was shown at 45oC (263.8 U/ ml), 50oC (263.8 U/ ml), 50 o C (473 U/ ml), and 55 o C (419.8 U/ ml), respectively ( Fig 6). The result obtained is similar to the report of Lima et al, (2004) who observed maximum activity of lipase produced by B. megaterium at 55 o C. Similarly, Faouzi et al, (2015) reported that lipase produced by B. pumilus exhibited optimum activity at 45 o C. The previous study of Lima et al, (2012) recorded that the optimum lipase activity has been found between 30-60 o C. Devi and Chary, (2018) attributed the higher enzyme activity observed at elevated temperatures to the increased kinetics of the enzymatic reactions. The thermostable lipases are very promising for industrial applications such as detergent formulations and other bio-transformations, since processes performed at high temperatures increase the reaction rate.…”
Section: Effects Of Temperature On Lipase Activitysupporting
confidence: 92%
“…Bacterial lipases are remarkably numerous and frequently described as thermo-stable and substrate non-specific (Dhake et al, 2013;Vaquero et al, 2016). Recent studies highlight the thermal stability and industrial potential of bacterial lipases, such as those from Thermophilic Bacterium, Bacillus licheniformis lipases (Rashid et al, 2013), Bacillus pumilus lipase isolated from tannery waters (Laachari, El Bergadi, et al, 2015), and extracellular lipase of Bacillus licheniformis (Rashid et al, 2013). For instance, the lipase Serratia marcescens N3 is used to hydrolyze several types of edible oils, and it is most active when applied to Gingily oil (Zaki & Saeed, 2012).…”
Section: Bacterial Lipasesmentioning
confidence: 99%